ISO 22000, an international standard for ensure food security in the market global (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The continued globalization of food supply chains means that compliance with private quality assurance schemes is often a prerequisite for companies to be accepted as suppliers, with the consequent complication arising when their aim is to deliver their products to different markets. In 2005, in order to overcome this drawbackwith the development of a standard to harmonize global requirements for a food safetymanagement system, ISO launched the ISO 22000 standard. A certification standardthat, with its international recognition and applicability to the entire food chainwithout exception, awards clarity and homogeneity to the food sector. Among theissues addressed in this work are its main features; the benefits and limitations associated with its implementation, as well as a reflection on its growing success andfuture.
Keywords: food safety; management systems; ISO 22000.